Attenuation of copaiba oil in hepatic damage in rats - Brito,Marcus Vinicius Henriques (2014)
PURPOSE: To investigate the copaiba oil on the hepatic damage induced by acetaminophen, comparing against corn oil. METHODS: Fifty four rats were distributed into nine study groups (N=6): control group, that didn't receive the acetaminophen; Acetaminophen Group, that only received the acetaminophen; Prophylactic Copaiba Group 1, that received copaiba oil two hours before the acetaminophen; Prophylactic Copaiba Group 7, that received copaiba oil seven days, once by day, before the acetaminophen; Therapy Copaiba Group, that received the copaiba oil two hours after the acetaminophen, the corn's groups were similar than copaiba oil groups; and N-Acetyl-Cysteine Group, that received the N-Acetyl-Cysteine two hours after the acetaminophen. Euthanasia was performed after 24 hours. The serum levels transaminases, bilirubin and canalicular enzymes were analyzed. RESULTS: The prophylactic copaiba group 7, therapy copaiba group and N-Acetyl-Cysteine Group showed amounts of AST and ALT similar to the control group; and the prophylactic copaiba group 1 and corn's groups showed similar levels to the acetaminophen group. There was no significant difference between the groups regarding the amount of alkaline phosphatase and ɤ GT (p>0.05). The therapy copaiba group showed the highest levels of total bilirubin and was statistically different from the other groups (p<0.01). CONCLUSIONS: Copaiba oil administered prophylactically for seven days and therapeutically 2 hours after the acetaminophen acute intoxication offered a potential hepato protection against paracetamol-induced hepatic damage, normalizing the biochemical parameters similarly to N-Acetyl-Cysteine, and the treatment with corn oil shows no effect on the liver damage.